2020
DOI: 10.1111/and.13704
|View full text |Cite
|
Sign up to set email alerts
|

Minocycline attenuates testicular damages in a rat model of ischaemia/reperfusion (I/R) injury

Abstract: Testicular torsion is one of the most significant urological disorders in which the spermatic cord is twisted along the longitudinal axis and affects the male gender at any age; however, newborns, children and adolescent boys are the main target of the disease (Fehér & Bajory, 2016). Epidemiological studies indicated that testicular torsion occurs between the ages of 13 and 16 years and/or during the first year of life (Pogorelic, Mrklic, Juric, Biocic, & Furlan, 2013). The incidence of the spermatic cord tors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 41 publications
2
10
0
Order By: Relevance
“…Prior investigations documented that the antioxidant enzymes can compensate for the destructive effect of free radical molecules by inhibiting mechanisms, and protect the testicular tissue from the ROS damages (Lanzafame et al, 2009). In correspondent with our study, Mahdi Azarabadi et al demonstrated that the administration of Minocycline could decrease the testicular apoptosis, ischaemia and reperfusion damage through decreasing the level of MDA as well as increasing the level of SOD (Azarabadi et al, 2020). Also Khaled Radad et al reported in a study that Minocycline improved neuronal degeneration and seminiferous tubular damage and reduced malondialdehyde levels.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…Prior investigations documented that the antioxidant enzymes can compensate for the destructive effect of free radical molecules by inhibiting mechanisms, and protect the testicular tissue from the ROS damages (Lanzafame et al, 2009). In correspondent with our study, Mahdi Azarabadi et al demonstrated that the administration of Minocycline could decrease the testicular apoptosis, ischaemia and reperfusion damage through decreasing the level of MDA as well as increasing the level of SOD (Azarabadi et al, 2020). Also Khaled Radad et al reported in a study that Minocycline improved neuronal degeneration and seminiferous tubular damage and reduced malondialdehyde levels.…”
Section: Discussionsupporting
confidence: 89%
“…In correspondent with our study, Mahdi Azarabadi et al demonstrated that the administration of Minocycline could decrease the testicular apoptosis, ischaemia and reperfusion damage through decreasing the level of MDA as well as increasing the level of SOD (Azarabadi et al, 2020). Also Khaled Radad et al reported in a study that Minocycline improved neuronal degeneration and seminiferous tubular damage and reduced malondialdehyde levels.…”
Section: Apoptosis Index (Tunel Assay)supporting
confidence: 88%
See 2 more Smart Citations
“…Based on PubMed publications, we also explore the potential mechanism of these drugs for the treatment of MERS. Minocycline suppresses the release of IL-1β by reducing the mRNA expression [ 69 ]. Azithromycin significantly inhibits IL-1β secretion by destabilizing mRNA levels and a dose-dependent manner [ 70–71 ].…”
Section: Resultsmentioning
confidence: 99%